An integrated crop and hydrologic modeling system to estimate hydrologic impacts of crop irrigation demands. (October 2015) - McNider, R.T.; Handyside, C.; Doty, K.; Ellenburg, W.L.; Cruise, J.F.; Christy, J.R.; Moss, D.; Sharda, V.; Hoogenboom, G.; Caldwell, Peter
Abstract: The present paper discusses a coupled gridded crop modeling and hydrologic modeling system that can examine the benefits of irrigation and costs of irrigation and the coincident impact of the irrigation water withdrawals on surface water hydrology. The system is applied to the Southeastern U.S. The system tools to be discussed include a gridded version (GriDSSAT) of the crop modeling system DSSAT. The irrigation demand from GriDSSAT is coupled to a regional hydrologic model (WaSSI). GriDSSAT and WaSSI are coupled through the USDA NASS CropScape data to provide crop acreages in each watershed. The crop model provides the dynamic irrigation demand which is a function of the weather. The hydrologic model responds to the weather and includes all other anthropogenic competing uses of water. Examples of the system include an analysis of the hydrologic impact of future expansion of irrigation and the real-time impact of short-term drought. Highlights: We built a gridded version (GriDSSAT) of the crop model DSSAT that estimates irrigation demand. We coupled irrigation demand to a regional hydrologic model (WaSSI). We incorporated USDA CropScape data to provide crop acreage in each watershed. We utilized the resulting tool to model the impact of irrigation withdrawals on surface water hydrology.